PTU-109 Immunosuppression; An Independant Risk Factor in Catheter Related Blood Stream Infections in Patients On Long Term Parenteral Nutrition?. (17th August 2016) - Oke, S; Ismail, D; Gabe, SM
Abstract : Introduction: Catheter related blood stream infections (CRBSI) are a serious complication for patients on home parenteral nutrition (HPN). 1 20% of patients on HPN at our institute take immunosuppressive medication. Little data is available to assess if immunosuppression confers any increased risk of CRBSI. We have therefore performed a retrospective cohort study on patients on HPN, cared for at St Mark's Hospital (Harrow) to assess if immunosuppression increases susceptibility to CRBSI. Methods: The Intestinal Failure Unit Database (a local database of all HPN patients) was interrogated between 01/01/2013 to 1/10/2015. Patients on HPN were divided into two arms; those with confirmed CRBSI and those without. The two groups were sub catagorised into immunosuppressed and non-immunosuppressed, and then catagorised by immunosuppression type and disease type. Results: A total of 149 patients (227 separate episodes) (age 18–86) with CRBSI & 170 patients (age 16–85) without CRBSI were identified. The distribution of disease types was broadly similar for both groups of patients with 39 (26%) patients with IBD, 26 (17%) with mesenteric ischaemia, 30 (20%) with motility disorders & 32 (21%) with surgical complications in the CRBSI group. This compared to 44 (26%) with IBD, 23 (14%) with mesenteric ischaemia, and 14 (8%) with motility disorder & 37 (22%) with surgical complications in the non CRBSI group. 25 (17%) of the CRBSI group were immunosuppressed while 39 (23%) in the non CRBSI group were immunosuppressed. For each disease subtype CRBSI was compared against immunosuppression status (Fisher's exact test). It was found that there was no statistical increase in risk in CRBSI with immunosuppression p = 0.07 (>0.05) (see table 1 ) No significant differences were seen according to the type of immunosuppression used (p = 0.6), or if patients were on dual or single immunosuppression (p = 1.0). Conclusion: Although there is a clinical assumption that immunosuppression is a risk factor for developing CRBSI, our large retrospective cohort study has shown that this does not appear to be an independent risk factor in the development in patients on HPN. Reference: 1 Buchman AL, Moukarzel A, Goodson B, Herzog F, Pollack P, Reyen L, Alvarez M, Ament ME, Gornbein J. Catheter-related infections associated with home parenteral nutrition and predictive factors for the need for catheter removal in their treatment. JPEN J Parenter Enteral Nutr 1994;18 (4):297–302. Disclosure of Interest: None Declared